The effect of FeMn and FeB additive on hematite (α-Fe2O3) and their characterization. (March 2019) - Ginting, M; Pane, J; Simbolon, D H; Simbolon, S; Yunus, M; Kurniawan, C; Sebayang, P
Abstract: In this study, the mineral material addition of FeMn and FeB to the hematite (α-Fe2 O3 ) by varying each mass concentration of 0, 4, and 8 wt.% have been prepared by powder metallurgy method. The mixing process of the powder was done by high energy milling (HEM) for 1 h. Then, the powders were calcined at temperature of 1000 °C for 2 h. The Effect of FeMn and FeB additives on α-Fe2 O3 causes the increasing of the particles diameter. The increasing of FeMn additive increases the powder density of material, but the addition of FeB decreases it. The material of α-Fe2O3with FeMn additive has dominant phases of α-Fe2 O3 and the minor phases of MnO2 and Fe3 O4 . The material of α-Fe2 O3 with FeB additive has two phases as magnetite (Fe3O4) and hematite (α-Fe2 O3 ). The magnetic properties of a α-Fe2 O3 material with FeMn and FeB additives decrease the saturation value and coercivity.